The Correlation Between Adolescent’ Mental Health Status and Parental Support: : A Quantitative Study - Isni, Khoiriyah; Amalia, Jihan Oktaviani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Parental social support serves as a protective factor for the mental health of adolescents. This study examines the correlation between parental social support—encompassing emotional, informational, instrumental, and companionship support—and the mental health condition of adolescents. Methods: This study employs a quantitative methodology utilising a cross-sectional design. Using purposive sampling, 93 unmarried teenagers aged 15 to 24 were selected as research respondents. The research instrument encompasses four categories of social support as delineated in Sarafino and Smith's theory, while mental health status is assessed using the DASS (Depression Anxiety Stress Scale) 21. Results: 50% of the participants perceived a lack of social support from their parents, while 76.3% reported experiencing mental health conditions. The lack of parental involvement in discussions with teenagers or professionals is frequently evident in findings. Conclusion: Consequently, stakeholders must collaborate across sectors to enhance parental involvement in mitigating adolescent mental health issues